Behavioural responses of reptile predators to invasive cane toads in tropical Australia. (1st November 2013) - Pearson, David J.; Webb, Jonathan K.; Greenlees, Matthew J.; Phillips, Benjamin L.; Bedford, Gavin S.; Brown, Gregory P.; Thomas, Jai; Shine, Richard
Abstract The ecological impact of an invasive species can depend on the behavioural responses of native fauna to the invader. For example, the greatest risk posed by invasive cane toads (Rhinella marina Bufonidae) in tropical Australia is lethal poisoning of predators that attempt to eat a toad; and thus, a predator's response to a toad determines its vulnerability. We conducted standardized laboratory trials on recently captured (toad‐naïve) predatory snakes and lizards, in advance of the toad invasion front as it progressed through tropical Australia. Responses to a live edible‐sized toad differed strongly among squamate species. We recorded attacks (and hence, predator mortality) in scincid, agamid and varanid lizards, and in elapid, colubrid and pythonid snakes. Larger‐bodied predators were at greater risk, and some groups (elapid snakes and varanid lizards) were especially vulnerable. However, feeding responses differed among species within families and within genera. Some taxa (notably, many scincid and agamid lizards) do not attack toads; and many colubrid snakes either do not consume toads, or are physiologically resistant to the toad's toxins. Intraspecific variation in responses means that even in taxa that apparently are unaffected by toad invasion at the population level, some individual predators nonetheless may be fatally poisoned by invasive cane toads.